(3QSGdI dHYV GdMceGA aj GdUfYI GdCdgjIs
(3ChdgG (B:s
(3Cf QCS GdJOHjQ hReGf GdCeQ hLfS GdONGf ai cd JUYjO hefY GdQjM ai ONhd GdBfjI s
(3BNQgG (B:s
(3hGMPQ GdZHGQ hGdbOQ hEjGc hGdYLdI hGMPQ GdCHWGA hGdZadI hGdSde JQTO Gf TGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHYs
(3HgG fXGe GdJYbjHIs
(3JdjI bhd dLGHQ Hf MjGf ai cJGH GdMLQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs